2016
DOI: 10.4322/acr.2016.054
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine-induced hypersensitivity myocarditis presenting as sudden cardiac death.

Abstract: Hypersensitivity myocarditis is a rare but serious adverse effect of clozapine, a commonly used psychiatric drug. We report the case of sudden cardiac death from clozapine-induced hypersensitivity myocarditis diagnosed at autopsy. A 54-year-old Caucasian male on clozapine therapy for bipolar disorder presented with a sudden onset of shortness of breath. Laboratory studies were significant for elevated N-terminal prohormone of brain natriuretic peptide. During his hospital stay, the patient died of sudden cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
0
5
0
3
Order By: Relevance
“…As demonstrated by Katta et al [70], CIM myocarditis may have the character of eosinophilic myocarditis. However, in contrast to other subtypes of eosinophilic myocarditis (such as in the course of the Churg-Strauss syndrome or hypereosinophilic syndrome), in myocarditis released by a hypersensitive reaction to clozapine, eosinophilia is observed in only about 62% of patients.…”
Section: Objawy I Przebieg Cim Oraz Wyniki Badań Dodatkowychmentioning
confidence: 87%
See 2 more Smart Citations
“…As demonstrated by Katta et al [70], CIM myocarditis may have the character of eosinophilic myocarditis. However, in contrast to other subtypes of eosinophilic myocarditis (such as in the course of the Churg-Strauss syndrome or hypereosinophilic syndrome), in myocarditis released by a hypersensitive reaction to clozapine, eosinophilia is observed in only about 62% of patients.…”
Section: Objawy I Przebieg Cim Oraz Wyniki Badań Dodatkowychmentioning
confidence: 87%
“…Jak wskazują Katta i wsp. [70] zapalenie mięśnia sercowego typu CIM może mieć charakter eozynofilowego zapalenia mięśnia sercowego. W przeciwieństwie do innych podtypów eozynofilowego zapalenia mięśnia sercowego (takich jak w przebiegu zespołu Churga-Strauss czy zespołu hipereozynofilowego), w zapaleniu mięśnia sercowego wyzwolonemu przez reakcję nadwrażliwości na klozapinę eozynofilię obserwuje się jedynie u około 62% pacjentów.…”
Section: Objawy I Przebieg Cim Oraz Wyniki Badań Dodatkowychunclassified
See 1 more Smart Citation
“…Возникновение жизнеугрожающих побочных эффектов отмечено также и при приеме терапевтических доз препарата. Среди них значимое место занимают неблагоприятные кардиальные эффекты, такие как миокардиты, кардиомиопатии, перикардиты, сердечная недостаточность, внезапная сердечная смерть [7][8][9][10][11]. A. Al-Wahab и соавт.…”
Section: Introductionunclassified
“…Occurrence of life-threatening side effects was also noted during intake of therapeutic doses of the drug. An important role among them belongs to adverse cardiac effects such as myocarditis, cardiomyopathy, pericarditis, heart failure, sudden cardiac death [7][8][9][10][11]. A. Al-Wahab et al revealed in an experimental study the increased levels of noradrenaline, adrenaline, troponins, creatine phosphokinase-MB, interleukins, tumor necrosis factor alpha, cytokines in the blood of mice that received Clozapine [12,13].…”
Section: Introductionmentioning
confidence: 99%